Prospects of Quantity Surveyor Undergraduate in Construction Sector - Tan, Wan Yu; Chan, Siew Chong (2016)
The roles of Malaysian Quantity Surveyors have progressively changed due to the changes of scales and complexity of construction projects. Undergraduate student are no longer limited themselves in doing measurement, contract administration and documentation, and pricing and estimation works, but they are requested to further expand and diversify their job scopes. Therefore, these high employability skills and abilities are assumed able to equip an undergraduate QS in order to stand a good chance at the competitive and global market in the construction sector. The objective of this research is to identify the expectation of construction employers on to the QSs’ skills and justify the extent of the QS contribution in the current and future construction market. The data is analysed mainlythrough descriptive data analysis, frequency analysis and weighted average index. Questionaire were distributed and collected from 29 respondents. The findings of this research shows that the expectations of construction employers onto both of the technical and soft skills of the fresh QS graduate are equally important, and thus, the future QS graduate should ensure to master these skills well in order to secure a career in the future construction industry.